2012
DOI: 10.1039/c2ce25547b
|View full text |Cite
|
Sign up to set email alerts
|

Coordination polymers of polyamine and macrocycles controlled by pyridine-containing arms

Abstract: N,N9-bis(3-aminopropyl)-3-pyridylmethylamine (bapa) has been synthesized as a building block for coordination polymers, and its coordination polymer {[Cu(bapa)(MeCN)][Cu(bapa)(ClO 4 )] (ClO 4 ) 3 ?MeCN} ' (1) was obtained by reacting it with Cu(ClO 4 ) 2 ?6H 2 O in MeCN solution. In addition, three macrocyclic coordination polymers, {), were obtained by the condensation between bapa and N,N9-bis(3formyl-5-methylsalicylimine)-1, 2-propylenediimine for 2 and 3, and N,N9-bis(3-formyl-5methylsalicylidene)-1,2-ethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…In our previous work, we found that Schiff base macrocyclic complex bearing 3-pyridylmethyl pendant can form coordination polymer by means of the coordination interaction between N atom in 3-pyridylmethyl and the metal ion in adjacent macrocyclic unit. 6 To continue our effort to obtain coordination polymer with polynuclear macrocyclic building blocks, a new macrocyclic ligand with two exible pendant arms, involving donor oxygen atoms, has been synthesized, shown in Scheme 1. The reaction of this macrocyclic ligand with nickel(II) acetate leads to a coordination polymer.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we found that Schiff base macrocyclic complex bearing 3-pyridylmethyl pendant can form coordination polymer by means of the coordination interaction between N atom in 3-pyridylmethyl and the metal ion in adjacent macrocyclic unit. 6 To continue our effort to obtain coordination polymer with polynuclear macrocyclic building blocks, a new macrocyclic ligand with two exible pendant arms, involving donor oxygen atoms, has been synthesized, shown in Scheme 1. The reaction of this macrocyclic ligand with nickel(II) acetate leads to a coordination polymer.…”
Section: Introductionmentioning
confidence: 99%